IMPLEMENTATION OF COMPREHENSIVE SEXUAL EDUCATION (CSE) FOR ADOLESCENTS IN THE SCHOOL EDUCATION CURRICULUM AS AN EFFORTS TO PREVENT CHILD MARRIAGE - AZIZAH, NUR; Pinandia Sustamy, Raffiky (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Adolescence is a transitional period from childhood to adulthood that is associated with various changes, including physical changes, cognitive changes, and psychosocial changes. In Bojonegoro Regency, the high rate of child marriage is caused by several factors, including economic factors, parental matchmaking, marriage by accident (pregnancy outside of marriage), educational factors, environment, and peers Method: This community service activity was carried out in several stages, including: preparation, implementation, namely the implementation of Comprehensive Sexuality Education, as well as evaluation and assessment of the results of the activity. Result: After carrying out this community service activity, it was shown that the level of understanding of adolescents regarding Comprehensive Sexual Education (CSE) was almost half of the adolescents had a poor level of understanding, namely 14 people (46.6%), whereas after carrying out the implementation of Comprehensive Sexual Education (CSE) activities, the level of understanding of adolescents increased, namely 18 people had a good understanding (60%). Conclusion : After carrying out this community service activity, it was shown that the level of understanding of adolescents regarding Comprehensive Sexual Education (CSE) was almost half of the adolescents had a poor level of understanding, namely 14 people (46.6%), whereas after carrying out the implementation of Comprehensive Sexual Education (CSE) activities, the level of understanding of adolescents increased, namely 18 people had a good understanding (60%).